Visionary Process towards Biotechnological Development - Arnáez-Serrano, Elizabeth (2019)
The Biotechnology Research Center (CIB), created in 1994, is the research unit of the School of Biology of the Costa Rica Institute of Technology. As a research entity, CIB offers a series of specialized technical services, which resulted from the knowledge gained through a growing number of research projects developed on three research fields: Plant Biotechnology, Environmental Biotechnology and Biomedical Applications. During the 25 years of its operation, researchers at CIB have shown a strong commitment towards creating science and technology with national and international impact. Additionally, the different cooperation initiatives between this center and other institutions are a clear example of the growth dynamics of this research unit, both in the number of projects and their scientific level, thus becoming a reference at national and regional level